Some aspects of the teaching of English as a main language at the secondary level with special reference to the question of 'language' - Crampton, Michael Edward (Rhodes University, Faculty of Education, Department of Education, 1984)
From Introduction: A training in English literature followed by a limited number of English method lectures on how to teach a prescribed Victorian novel proved inadequate in these circumstances. Moreover, several years of interaction with colleagues in staff rooms, conferences and seminars in England and South Africa failed to yield a secure sense of purpose or a confident understanding of why, when and how to teach what in the English lesson. Too many amateurs are employed to teach English. Barn dancers might as well teach ballet. Yet for all that, there grew a conviction, reinforced by the vital involvement of many inspiring colleagues, that English teaching is the mainspring of the educational process where that language is the medium of education. The hope of making some contribution to the advancement of the English teaching profession, especially for the benefit of those who look up, hoping to learn, is sufficient motivation for this work. The endeavour will be, in the first place, to review some traditional aspects of English teaching in their historical context. A description of the traditional sources upon which the profession intuitively draws might assist in explaining the existence of certain attitudes. In chapters 2-4 an analysis of current thinking, directions and practices will aim to explore some aspects of what English teaching in schools is, when and how it happens and to what end. The direction in which the profession is moving will be weighed against the relevance of school English in the further learning experiences of school leavers before conclusions and recommendations are listed. Throughout, the purpose will be to contribute insights into the practice of teaching English as a main language. The term 'main language' has been deliberately chosen. Growing numbers of South Africans might be described as English L2 'main language' speakers in the sense that though Afrikaans, Zulu, Xhosa or Gujarati might be regarded as their 'first' language , English is the language which they mainly use in the ordinary business of life, in the home, at work and at play. The situation is fluid and interactive. Many adult speakers are in the process of assuming English as a main language. Small groups at work (and increasingly in lecture halls and classrooms) might, in learning contexts use English mainly as a means of interaction but include a variety of native Ianguage speakers from Armenian to ZuIu. The concept of English as a 'main' as distinct from 'first' or 'second' language seems to be gaining fresh significance. The fact that it is no longer safe to assume that main language English speakers will all be drawn from uniform speech communities, has major implications for the teaching of the subject; implications that will rapidly become more significant with the eradication of apartheid from our society. In this study, focus will be upon the teaching of the subject at the secondary level. Within that area particular emphasis will fall upon the final three years of schooling. With the approach of the matriculation examination many schools begin to rattle their shackles, bringing 'English specialists' to bear on prescribed works and increasing the intensity of tests and mock examinations. The leisurely dalliance with projects and casual affairs with creative work associated with English in the early years, can be forgotten as attention is confined with increasing intensity on possible examination questions . Thus the opportunity to finish what has been begun is often wasted. Where added impetus and direction could be given in the final years to interest, enjoyment and abilities fostered at primary and junior secondary levels, preoccupation with an irrelevant literary erudition, with disjointed comprehension passages and spurious essay topics, can stifle natural growth. On the other hand it must be acknowledged that the impetus provided by the final examination can channel energy and produce insights that might otherwise have remained dormant. Thus, while the final three years of schooling are educationally no more important than any other phase in the twelve years schooling, they do III involve important issues within the writer's range of experience.
Keywords: English language -- Study and teaching (Secondary)